The Effect of Advance Organizer Model on Physics Learning Outcomes in Terms Prior Knowledge - Harjono, Ahmad; Hikmawati, Hikmawati; Putra, I Ketut Eka (Pascasarjana, Mataram University, 2024)
This research is experimental research which aims to determine the effect of the advance organizer model on physics learning outcomes in terms of prior knowledge. This research uses a one group pretest-posttest design type . The sample in this research was class X MIA 1 SMAN 8 Mataram which consisted of 24 students. The data collection technique uses test sheets in the form of pre-test and post-test given before and after treatment. The pre-test data results were obtained with an average of 35.6 and 81.5 for the post-test average . The results of the prerequisite test with the Shapiro Wilk test showed that the pre-test and post-test data were normally distributed. Then, a t-test was carried out using a paired sample t-test showing a significant value (sig. 2 tailed) of 0.000, which means (sig. 2 tailed) < 0.005 so it can be concluded that there is an influence of the advance organizer learning model on physics learning outcomes in terms of priors knowledge.